End of project evaluation Canada-University of the West Indies Institutional Strengthening Project - SALASAN Associates Inc. (SALASAN Associated Inc. SidneyCA, 1998)
Presents the end of project evaluation of a project which sought to strengthen the University of the West Indies capacity to respond to critical Caribbean regional development needs. Makes recommendations.